Trust in Testimony. Children ? s Use of True and False Statements - Koenig, Melissa; Clément, Fabrice; Harris, Paul (My University, 2004)
The extent to which young children monitor and use the truth of assertions to gauge the reliability of subsequent testimony was examined. Three- and 4-year-old children were presented with two informants, an accurate labeler and an in-accurate labeler. They were then invited to learn names for novel objects from these informants. The children correctly monitored and identified the informants on the basis of the truth of their prior labeling. Furthermore, children who explicitly identified the unreliable or reliable informant across two tasks went on to demonstrate selective trust in the novel information provided by the previously reliable informant. Children who did not consistently identify the unreliable or reliable informant proved indiscriminate.